WORK SAMPLING OF A PROFESSOR DURING "OFF-CONTRACT" PERIODS. - BRINK, JAN; MCDONALD, DALE (College Student Journal, 2011)
This research paper studies how the time of a professor is used during the summer when he is off contract. The professor used an industrial engineering technique called work sampling to gather data. This professor is under a 9 month contract as many people in academia are and technically is off for the next three months. It is a pretty well known fact in the academic world that nearly all professors, that have nine month contracts, do work during this three month period. One of the authors did a self study to see how his time is used in the summer time. This information is useful for him and also for the administration. This kind of study could also be done by others that are in a similar situation.